DEVELOPMENT OF GAS KINETIC THEORY LEARNING TOOLS: 5E & BRICK MAKING FOR COMPUTATIONAL THINKING - Ni'mah, Ayu Mar'ati Barokatun; Jumadi, Jumadi; Afifah, Reny; Supahar, Supahar (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
This research aims to (1) develop feasible learning tools for the kinetic theory of gases and (2) create effective physics learning tools for students. The research employs the ADDIE model. The data analysis to evaluate the feasibility and practicality of the learning tools uses a standard scale, while the validity of the question instrument is assessed using Aiken's V and item analysis with the Partial Credit Model (PCM). To measure the effectiveness of the tools in enhancing students' computational thinking skills, a repeated-measures MANOVA is conducted using the General Linear Model (GLM) with a significance level of 0.05. The findings indicate that (1) the developed learning tools are deemed feasible for use in improving computational thinking skills, as assessed by media experts, material experts, and practitioners. Moreover, (2) the analysis shows a significance value of 0.000 < 0.05, meaning there is a noticeable difference in computational thinking abilities between the experimental and control groups. Additionally, the effect size obtained was 0.813, which is categorized as large. These results suggest that the learning tools developed are both feasible and effective. In conclusion, this research demonstrates the potential of these tools to enhance students' computational thinking abilities in physics education, specifically in the context of the kinetic theory of gases, making them a valuable resource for future learning activities.